PENGARUH SALINITAS TERHADAP METABOLISME KEPITING BAKAU (Scylla olivacea) - Muhammad Yusri Karim (Universitas Gadjah Mada, 2008)
The aim of this research was to know the effect salinity on metabolism of mud crab (Scylla olivacea). The research was carried out in circular plastic tanks consist of water at amount 16 l in closed system. The expriments were done using complete randomized design with 4 treatments and 3 replication. The salinity treatments were: (A) 5, (B) 15, (C) 25 and (D) 35‰. The Test animal used were female mud crab with average body weight was 20 ± 0,5 g that stocked by three individuals per tank. Analysis variance and Tukey test were used to reveal the effect of treatments. The result showed that salinity was significantly (p < 0,01) affect to basal, feeding, routine metabolism and SDA (Spesific Dynamic Action). The highest value of mud crab basal metabolism rate was 0.17 kJ/g body weight/day produced at salinity 5‰ and the lowest was 0.14 kJ/g body weight/day. The highest value for feeding, routine metabolism rate and SDA of mud crab produced at 25‰ with 0.49; 0.42 dan 0.35 kJ/g body weight/day, respectively, and the lowest were 0.47; 0.37 dan 0.30 kJ/g body weight/day that resulted by salinity of 5‰. For culture purpose of mud cab, it is recommended to use the salinity level of 25‰.